Interaction of soil water storage dynamics and long-term natural vegetation succession on the Loess Plateau, China - Zhang, Yong-wang; Deng, Lei; Yan, Wei-ming; Shangguan, Zhou-ping (Catena (Giessen), 2016)
Soil water is a key terrestrial water resource, particularly in arid and semi-arid regions of the world such as the Loess Plateau of China. Information on the dynamics of soil moisture following vegetation restoration is essential for managing water resources and can be helpful for adjusting relevant government policies. To evaluate the response of soil water storage (SWS) to long-term natural vegetation succession (~160a), we examined the soil moisture for different restoration ages in the Ziwuling forest region, which is located in the central part of the Loess Plateau. Our results showed that the SWS decreased with long-term natural vegetation restoration. The bulk density (BD), soil water content (SWC), and clay and silt content presented similar trends to those of the SWS throughout the entire vegetation succession. The SWS was significantly and positively correlated with the SWC and aeration porosity (P<0.05). The SWC was lower in the upper soils (0–50cm) than in the deeper soils (>50cm) at every restoration stage, as was the SWS; however, the SWS in the 200–300cm soil layer was the highest (164.61–212.80mm) compared to other layers in all restoration stages. These results are expected to help improve the understanding of the response of deep soil water to long-term natural vegetation restoration and to provide insights into the dynamics of deep soil water influenced by vegetation. •The soil water storage decreased along with the natural vegetation succession.•The soil total porosity and capillary porosity strongly affect the soil water content in the vegetation restoration process.•The soil water storage was highest in the 200–300cm soil layer at each restoration stage.